2017
DOI: 10.1103/physrevfluids.2.124601
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of turbulent-jet wave packets and their acoustic efficiency

Abstract: This paper details the statistical and time-resolved analysis of the relationship between the near-field pressure fluctuations of unforced, subsonic free jets (0.4 M 0.6) and their far-field sound emissions. Near-field and far-field microphone measurements were taken on a conical array close to the jets and an azimuthal ring at 20• to the jet axis, respectively. Recent velocity and pressure measurements indicate the presence of linear wave packets in the near field by closely matching predictions from the line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…But careful observation reveals that the hydrodynamic region of the jet comprises an organised structure: there exist coherent, high-amplitude oscillations, saturated in black and white in Figure 1, and that have the form of a wavepacket. This coherent-structure signature has been observed and studied experimentally for over 50 years [9,10,11,12,13,14]; a recent observation by Breakey et al [14] is shown in section 3 ( Figure 6).…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…But careful observation reveals that the hydrodynamic region of the jet comprises an organised structure: there exist coherent, high-amplitude oscillations, saturated in black and white in Figure 1, and that have the form of a wavepacket. This coherent-structure signature has been observed and studied experimentally for over 50 years [9,10,11,12,13,14]; a recent observation by Breakey et al [14] is shown in section 3 ( Figure 6).…”
Section: Introductionmentioning
confidence: 70%
“…3.3.4 Spectral Proper Orthogonal Decomposition (ex-ample7.m, example8.m) We now further evaluate the statistics of the stochastic source by taking spectral POD of the CSD in eq 46, using the approach described in section 2.4.2. Figure 14 [14,17], shows that rank reduction is possible with a small number of modes. The first four modes for this case are shown in figures 15 and 16 14 .…”
Section: Acoustic Matching (Example6m)mentioning
confidence: 99%
See 3 more Smart Citations